(untitled) (American Journal of Technology and Applied Sciences, 2023)
This article provides for the study of the effectiveness of educational technology when integrating into the credit module system. Distinguished by its modular structure and flexibility, the credit module system has gained popularity in educational institutions around the world. By mastering educational technology such as online platforms, multimedia resources, interactive learning tools, educators can communicate with students and increase academic performance. In this review, existing research on the subject will be studied within the framework of the credit module system to provide insights into the benefits and possible difficulties of applying educational technology.